2022
DOI: 10.1037/pspp0000401
|View full text |Cite
|
Sign up to set email alerts
|

An integrative framework for conceptualizing and assessing social, emotional, and behavioral skills: The BESSI.

Abstract: People differ in their social, emotional, and behavioral (SEB) skills: their capacities to maintain social relationships, regulate emotions, and manage goal-and learning-directed behaviors. In five studies using data from seven independent samples (N = 6,309), we address three key questions about the nature, structure, assessment, and outcomes of SEB skills. First, how can SEB skills be defined and distinguished from other kinds of psychological constructs, such as personality traits? We propose that SEB skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
122
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(141 citation statements)
references
References 82 publications
13
122
0
6
Order By: Relevance
“…In addition to optimism, energy and trust were the other two important skills for psychological health outcomes. Energy, the capacity to be active and enthusiastic in daily pursuits, is closely associated with high levels of physical activities (Soto et al, 2022), thus leading to better subjective well-being (Bell et al, 2019; Hyde et al, 2013). People with high levels of trust skills tend to have higher subjective well-being and life satisfaction by possessing positive social relationships and high social capital (Helliwell et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to optimism, energy and trust were the other two important skills for psychological health outcomes. Energy, the capacity to be active and enthusiastic in daily pursuits, is closely associated with high levels of physical activities (Soto et al, 2022), thus leading to better subjective well-being (Bell et al, 2019; Hyde et al, 2013). People with high levels of trust skills tend to have higher subjective well-being and life satisfaction by possessing positive social relationships and high social capital (Helliwell et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This also exists in many other social–emotional skill and personality measures (see Abrahams et al, 2019 for more discussion). Recently, Soto et al (2022) developed a social–emotional skill measurement in which skills were identified and measured as functional capacities: How someone is capable of thinking, feeling, or behaving when the situation calls for it (e.g., how well you can do a specific thing ), which is distinctive from personality traits referring to how someone tends to think, feel, and behave when averaged across situations. They showed that the proposed skills are empirically distinguishable from personality traits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, some individuals are more successful at persuading, showing compassion, or calmly dealing with criticism than others. Differences in such social skills have frequently been discussed as key person variables related to pivotal outcomes, such as academic success and job performance ( Arthur et al 2003 ; Ferris et al 2001 ; Lievens and Sackett 2012 ; Soto et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%